Family Quality of Life Survey (FQOLS-2006): Evaluation of Internal Consistency, Construct, and Criterion Validity for Socioeconomically Disadvantaged Families. (1st January 2018) - Samuel, Preethy S.; Tarraf, Wassim; Marsack, Christina
ABSTRACT: Aims : The purpose of this study was to test the psychometric properties of the Family Quality of Life Survey (FQOLS-2006) when used with urban families predominantly from socioeconomically disadvantaged backgrounds. Methods : Data gathered from 193 family caregivers using the FQOLS-2006 were subjected to reliability analyses, confirmatory factor analyses, and correlational analyses to test the internal consistency of the scales (reliability), factor structure of the scales (construct validity), and convergence between the long and short versions of the tool (criterion validity). Results : Internal consistency of the 54-item total FQOL scale was excellent ( α = .89), while that of the six-item domain subscales ranged from moderate to strong ( α = .46–.81). Although the subscale-level FQOL factor structure demonstrated good fit, some of the item-level factor loadings within each of the domains were low. Correlations between scores derived from the long and short versions ranged from moderate to strong ( r = .37–.73). Conclusions : Although the internal consistency of the scales ranged from moderate to strong, the FQOLS-2006 had only a moderate degree of construct and criterion validity when used with a sample consisting predominantly of minorities from socioeconomically disadvantaged backgrounds.